2009
DOI: 10.1021/jf902752t
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Aglycone, Vitamin K2 and Superoxide Dismutase Activity of Black Soybean through Fermentation with Bacillus subtilis BCRC 14715 at Different Temperatures

Abstract: In the present study, the change in the content and activity of some functional constituents including aglycone, the bioactive form of isoflavone, vitamin K2, and superoxide dismutase (SOD) of black soybeans during their solid fermentation with Bacillus subtilis BCRC 14715 at different temperatures (35, 40, 45, and 50 degrees C) for 18 h was investigated. It was generally found that fermentation resulted in an enhancement of these constituents, regardless of fermentation temperature, while varying the fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…In the present study, using continuous feeding of isoflavone glycosides, we found that the percentage isoflavone deglycosylation in continuous bioconversions was higher than 90%, and the concentrations of daidzein and genistein were, respectively, about 40-fold and 12-fold higher than those reported in fermented soymilk using L. paracasei BCRC 14023 (Wei et al 2007) or S. thermophilus BCRC 14085 (Chien et al 2006). In addition, two other B. subtilisrelated researches, which are limited in solid-state fermentation, have been reported (Hu et al 2010;Wu and Chou 2009). Black soybean fermented by B. subtilis BCRC 14715 at 50°C for 18 h showed increased production in total isoflavone aglycone, and it was determined to be 110.75 μg/g.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, using continuous feeding of isoflavone glycosides, we found that the percentage isoflavone deglycosylation in continuous bioconversions was higher than 90%, and the concentrations of daidzein and genistein were, respectively, about 40-fold and 12-fold higher than those reported in fermented soymilk using L. paracasei BCRC 14023 (Wei et al 2007) or S. thermophilus BCRC 14085 (Chien et al 2006). In addition, two other B. subtilisrelated researches, which are limited in solid-state fermentation, have been reported (Hu et al 2010;Wu and Chou 2009). Black soybean fermented by B. subtilis BCRC 14715 at 50°C for 18 h showed increased production in total isoflavone aglycone, and it was determined to be 110.75 μg/g.…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteria, yeasts and moulds were not detected throughout BS. In steamed black soybean, Wu and Chou (2009) found that B. subtilis BCRC 14715 grew rapidly at 30-50°C reaching 9.5 logs CFU/ml after 18 h, regardless the cultivation temperature. Values are means of three independent fermentations ± standard deviation.…”
Section: Growth and Acidification Activity Of Microbial Populations Dmentioning
confidence: 96%
“…The ssf procedure used has been described previously [6]. Briefly, the initial moisture content was adjusted at 50% by addition of sterilized C361 water to the autoclaved substrate that was kept in a fridge (4 • C) overnight to allow complete swelling of the granules. Fermentation was carried out at 37…”
Section: Substrate Preparation and Fermentationmentioning
confidence: 99%